What are Electronic Communications and their Argument for Proof in the Light of the Corona Pandemic in Accordance with the Provisions of Bahrain’s Electronic Communications and Transactions Act No. (54) Of 2001 - et. al., Mohammad Abdalhafid Alkhamaiseh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The world is witnessing today a great revolution in the field of electronic information and communications, which included various aspects of life, and one of the most important areas affected by this technological revolution is the field of electronic transactions. Corona", which increased the importance of remote dealing by electronic means to limit the outbreak and spread of this epidemic. At the end of this research, we have concluded many results and recommendations, which we hope will be of interest to the legislator.